ANALYSIS OF MURABAHAH FINANCING IMPLEMENTATION IN REPLANTING OIL PALM PLANTATIONS WEST PASAMAN DISTRICT(Case Study of PPP Perintis West Pasaman Regency) - Nafisah Nursapni; Zuwardi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
This research is motivated by problems in murabahah financing in the rejuvenation of oil palm plantations. The aim of this research is to determine and analyze the implementation of murabahah financing in the rejuvenation of oil palm plantations in West Pasaman district and to determine the effect of implementing murabahah financing in the rejuvenation of oil palm plantations in increasing the income of KPS Perintsi members. This research uses a qualitative descriptive type. The data sources in this research are primary and secondary data. Data collection techniques were taken through observation, interviews and documentation. The data analysis techniques are data reduction, data presentation, drawing conclusions. The results of the research obtained by the author show that the use of implementing murabahah financing in rejuvenating oil palm plantations of KPS Perintis members uses Bank Syariah Indonesia funds, namely murabahah loans for which KPS Perintis is channeling. Rejuvenation is carried out independently, except when felling oil palm trunks using the services of contractors using heavy equipment. Technically, the entire implementation of cultivation and financing for rejuvenation of oil palm plantations is from KPS Perintis which is the channeling until the plants produce, KPS Perintis is the person responsible for the loan installments which are deducted from the FFB production every month. The obstacle that occurs in the implementation of murabahah financing for the rejuvenation of oil palm plantations is that when signing the credit agreement for members whose parents have died and the SHM guarantee after changing the names to all the heirs, they have to collect the requirements of all the heirs. All heirs must sign the credit agreement for the disbursement of murabahah contract funds because each heir is domiciled in several regions, districts, and even in other provinces. The solution to this problem is to contact all the heirs whose names are listed in the SHM guarantee to come to the BSI office and there are some heirs who are unwilling or have problems coming to the BSI or KPS Perintis office, so KPS Perintis must go to the location where the heirs live.